Exploring Plant Species in Vietnam for the Production of pH Indicator Paper - Lê, Thị Thanh Trân (2023)
Purple cabbage, turmeric, magenta, amaranth, and red beet contain colour anthocyanins. These colours change according to pH environments. This research aims to explore the potential of utilizing various plant species, such as purple cabbage, turmeric, magenta, amaranth, and red beet, to develop pH indicator paper. The colour solutions of these plants were extracted with deionized water. The extracted solutions were analyzed by IR spectra and UV-Vis spectra. The peak of OH, C=O, and C-O in IR spectra changed in alkaline, neutral, and acidic environments, respectively. The maximum absorption wavelengths of the extracted solutions in UV-Vis spectra were 533 nm and 600 nm in alkaline and neutral environments, respectively. The pH indicator paper was created by impregnating plain white computer paper with extract solutions to achieve uniform colouration. These prepared pH indicator papers were used to detect the pH of household chemicals, including milk, soap, toothpaste, and various fruits and vegetables. The study demonstrates that these plant species exhibit excellent sensitivity to different pH values, possess good durability, and remain unaffected by environmental factors. The developed pH indicator paper holds promising practical applications for testing the pH of diverse chemicals. In this study, the pH indicator paper was employed to determine the acidity or alkalinity levels of commonly found household items, including fruits, beverages, and cleaning solutions. The results highlight the versatility and convenience of utilizing plant-based pH indicator paper for monitoring pH variations in daily life applications